Laporan kasus selulitis pedis pada diabetes melitus tipe 2 dengan terapi antibiotik dan insulin - Julaeha Julaeha; Nadya Farisma (Journal Borneo, 2022)
Diabetes mellitus (DM) is called the silent killer which can cause microvascular and macrovascular complications. Cellulitis is a form of microvascular complication of uncontrolled DM. A 49-year-old female patient came to the hospital with complaints of sores and pain in the right big toe. The patient has a history of type 2 diabetes mellitus, with the result of a current blood sugar level of 582 mg/dL. The patient received insulin therapy novorapid® and levemir®, paracetamol injection, ceftriaxone injection, metronidazole injection and amlodipine. From the results of monitoring drug therapy, administration of combination therapy with antibiotics and insulin is the right and safe choice of therapy in overcoming gangrenous infections with uncontrolled blood glucose conditions. However, in monitoring drug therapy, it was found that there was a potential for minor drug interactions between metronidazole and paracetamol. Metronidazole can increase the level or effect of paracetamol by affecting the metabolism of the liver enzyme CYP2E1 so there must be a delay in administration. Topical antibiotics should be considered in the long-term treatment of complications of cellulitis pedis in type 2 DM patients.